A revision of the genus fockea endl. (Asclepiadaceae) - Court, Doreen (Rhodes University, Faculty of Science, Botany Department, 1982)
A taxonomic revision of Fockea Endl. (Asclepiadaceae) is presented in which 5 species are recognised. Descriptions, illustrations and a key to the species are provided. F. comaru (E. Mey.)N.E.Br. is presented sensu lato, and because of its earlier publication in 1838 takes priority over F. angustifolia K. Schum. which was described in 1893. Historical and ecological notes on the genus are given and phylogenetic conclusions drawn.,KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Asclepiadaceae